Aptitude to Interpreting: Preliminary Results of a Testing Methodology Based on Paraphrase - Russo, Mariachiara; Salvador, Pippa (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis article presents the first results of a longitudinal study involving a sample of 46 students of the SSLMIT of Trieste. The study aims at developing an aptitude test for candidates to Conference Interpreting courses at university level. The test is based on an exercise of simultaneous paraphrasing. The linguistic analysis of the performances at syntactic, semantic and pragmatic levels has shown statistically significant correlations between the test results, the marks of interpreting exams and the time spent by the students to complete their training in interpreting.